Normative values for peripheral electrical gastroenterocolonography - Butov, M A; Shurpo, E M; Kuznetsov, P S; Dzhurzhevich, M D (Terapevtic̆eskii arhiv, 2015)
To elaborate the normative values of peripheral electrical gastroenterocolonography (EGECG). Fifty apparently healthy young people (14 women and 36 men; mean age 20.2 ± 4.7 years) were examined. Peripheral EGECG was used to study the motor-evacuating function of the gastrointestinal tract (GIT). The values of the main indicators and coefficients of GIT electrical activity were defined; the concepts of normal physiological values for GIT electrical activity were identified and their values were determined. Peripheral EGECG makes it possible to significantly estimate the bioelectrical activity of the gut. The informative markers of peripheral EGECG are relative electrical activity, ratio coefficient, rhythmicity coefficient, as well as the average amplitude and frequency of bioelectrical activity.